2021
DOI: 10.1016/j.ajem.2021.08.077
|View full text |Cite
|
Sign up to set email alerts
|

Predicting 30 – Day outcomes in emergency department patients discharged with COVID-19

Abstract: Introduction Determining disposition for COVID-19 patients can be difficult for emergency medicine clinicians. Previous studies have demonstrated risk factors which predict severe infection and mortality however little is known about which risk factors are associated with failure of outpatient management and subsequent admission for COVID-19 patients. Methods We conducted a retrospective observational chart review of patients who had a confirmed positive COVID-19 test c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
0
8
0
1
Order By: Relevance
“…Several prior studies used longer intervals including 7, 13 , 16 14, 14 or even 30 days. 5 , 7 , 10 , 12 We felt that a rule predicting outcomes within 72 hours of ED assessment might convey a more appropriate assessment of immediate risks that might be mitigated with decisions made in the ED, specifically around the decision to admit at the index visit. The 72‐hour interval is commonly used as a health care quality metric for patient recidivism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several prior studies used longer intervals including 7, 13 , 16 14, 14 or even 30 days. 5 , 7 , 10 , 12 We felt that a rule predicting outcomes within 72 hours of ED assessment might convey a more appropriate assessment of immediate risks that might be mitigated with decisions made in the ED, specifically around the decision to admit at the index visit. The 72‐hour interval is commonly used as a health care quality metric for patient recidivism.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2 , 3 , 4 Prior work has identified several clinical factors associated with progression to severe COVID‐19 disease. 5 , 6 , 7 , 8 , 9 , 10 The application of these findings to individual patients to support bedside decision‐making is not intuitive. Clinical decision rules (CDRs) involve the transformation of observed associations between various clinical features and outcomes into a “rule” or score that can be used to risk‐stratify patients and directly support bedside clinical decision‐making with individualized risk estimates.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have reported the association between the need for hospitalization among COVID-19 patients initially discharged from ED for ambulatory care and differents factors, including time from onset of symptoms, demographics such as age ≤ 48 years, symptoms such as fever and comorbidities such as COPD, hypertension, cognitive impairment, diabetes mellitus, coronary artery disease and chronic kidney disease (6,7,11,12). Although some studies have reported the value of emerging biomarkers, such as soluble urokinase plasminogen activator receptor (suPAR) and mid-regional pro-adrenomedullin (MR-proADM), for a safe discharge of COVID-19 patients in an ED (9,14), This study has some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…eligible patients, health records underwent individual chart review by a ED physician to extract the following data, selected from literature(4)(5)(6)(7)(8)(9)(10)(11)(12): demographics, previous comorbidities, laboratory tests on admission to ED, vaccination status and outcome data.Laboratory assaysSamples were analysed for sodium and potassium ions, by indirect potenciometry on Cobas ISE analyzer (Roche Diagnostic, Germany); creatinine, by a colorimetric assay (Jaffe reaction); C-reactive protein (CRP), by an immunoturbidimetric assay; lactate dehydrogenase (LDH), by an ultraviolet assay (lactate to pyruvate, traceable to IFCC method) and alanine aminotransferase (ALT), by a method according to IFCC without pyridoxal phosphate activation, on Cobas c702 (on G600II analyzer (Fujirebio Diagnostics Inc. Japan); D-dimer, by immunoturbidimetry on ACL-TOP Family (Instrumentation Laboratory, US) analyzers; and cell blood count by flow cytometry on Sysmex XN (Sysmex, Japan) analyzers(13).Statistical analysisContinuous variables were tested for normal distribution using the Kolmogorov-Smirnov or Shapiro-Wilk tests, as appropriate. Data were described as numbers and percentages for categorical variables and as medians (interquartile ranges IQR) or mean (standard deviation[SD]) for continuous data.…”
mentioning
confidence: 99%
“…Adults aged 65 years and older are 8.7 times more likely to require hospitalization for SARS‐CoV‐2 infection, and have accounted for 22% of cases and 78% of deaths related to COVID‐19 in the United States. 1 Older adults are thought to have unique vulnerability to COVID‐19 due to a higher comorbidity burden, 2 , 3 , 4 greater clinical frailty, 5 access to care challenges, 6 and immunosenescence, 5 , 7 all which could explain their greater likelihood of morbidity and mortality. Another possible explanation is that diagnoses of COVID‐19 could be missed in older adults due to less common presenting symptoms leading to treatment delay.…”
Section: Introductionmentioning
confidence: 99%